Albert Adams and the Deposition of Christ. Issue 1 (2nd January 2018) - Law-Viljoen, Bronwyn
Abstract: The large painting, South Africa 1958–1959 (Deposition) (1959) and four small etchings, all 1955, on the Deposition of Christ, form the basis of a discussion of the place of Albert Adams in the canon of South African art and of this artist's re-interpretation of a key image in Christian iconography and Western painting. In particular, the paper focuses on Adams's Deposition images as particular instantiations of his concern with the formal and philosophical challenges encountered by the artist in renditions of psychological and physical torment.